SAR Image Classification Using Multifractal Using Dimensions and Binary Cliques Iterative Decomposition Method - Teng, Hse Tzia (2009)
This research is intended to develop a reliable fractal geometry based method that is useful for the analysis and characterizarions of image processing applications in remote sensing.